Творческий характер юридической педагогики - Овчинникова, Альбина Петровна; Овчиннікова, Альбіна Петрівна; Ovchinnikova, Al'bina (My University, 2011)
In article is conducting parallel between theatrical and legal pedagogies. There is idea of the use the actor's methods in activity of the teacher of legal discipline.
Овчинникова А. П. Творческий характер юридической педагогики / А. П. Овчинникова // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 288-295.
Keywords: творчество; театральная педагогика; юридическая педагогика; тренинг; творчість; театральна педагогіка; юридична педагогіка; тренінг; creation; theater pedagogy; legal pedagogy; training